High Prevalence of Diarrhoegenic Intestinal Parasite Infections among Non-ART HIV Patients in Fitche Hospital, Ethiopia - Adamu, Haileeyesus (Public Library of Science, 2013)
BACKGROUND: HIV infection has been modifying both the epidemiology and outcome of parasite infections. Hence, this study was undertaken to determine the prevalence of Cryptosporidium and other intestinal parasite infections among HIV positives with and without Antiretroviral Treatment(ART) and its association with CD4+ T-cell count. METHODS: A cross-sectional study was conducted at Fitche hospital focusing on HIV positives who came to hospital for follow-ups. A total of 378 HIV positive persons with and without ART participated in the study. Data on socio-demographic factors and diarrhoea status were obtained by interviewing all 214 with ART and 164 without ART. Stool samples were collected from all patients and examined for intestinal parasites using direct, formol-ether and modified acid-fast staining techniques. RESULTS: The prevalence of intestinal parasite infections in this study was significantly higher among HIV positive persons not on ART. Specifically, the rate of infection with Cryptosporidium species, Blastocystis spp., Giardia lamblia, and Entamoeba histolytica/E. dispar were higher, particularly in those with CD4+ T-cell counts less than 200 cells/µL. Fifty seven percent of the study participants were on ART. Out of these 164/378 (43%) of the non-ART study participants were infected with at least one intestinal parasite species. Significant association was observed between lower CD4+ T-cell count (<200 cells/µL) and the prevalence of Cryptosporidium spp. and Blastocystis spp. The two parasites were significantly more prevalent in HIV positive non-ART patients. CONCLUSION: HIV infection increased the risk of having Cryptosporidium and other intestinal parasites and diarrhoea. Therefore, raising HIV positive’s immune status and screening for intestinal parasites is important. This study showed that patients who are taking ART had a lower prevalence of diarrhoea causing parasites and Cryptosporidium suggesting that ART through improvement of immune status of the patients may have contributed to controlling diarrhoea-causing parasites in HIV positive patients.